A Prospective Cross-sectional study to evaluate the utility of Fibroscan and Serum Biomarkers (APRI, FIB-4) for Non-Invasive Diagnosis of Liver Fibrosis in Metabolic dysfunction associated fatty liver disease (MAFLD) patients in a tertiary care center - S, Aravinth.; Rao, V.R. Mohan; P. R, Sobia. (Journal of Neonatal Surgery, 2025)
Introduction: Metabolic dysfunction associated fatty liver disease (MAFLD) is a more prevalent condition and a leading cause of chronic liver disease worldwide. It spans a spectrum from simple steatosis to metabolic dysfunction associated steatohepatitis (MASH), which can progress to fibrosis, cirrhosis, and hepatocellular carcinoma. Liver biopsy, the gold standard for diagnosing fibrosis, is invasive, costly, and carries risks, leading to a demand for non-invasive alternatives. FibroScan measures liver stiffness, while serum biomarkers, including the aspartate aminotransferase to platelet ratio index (APRI) and the fibrosis-4 (FIB-4) score, are inexpensive and accessible diagnostic options. This study aims to evaluate and compare the diagnostic accuracy of these non-invasive tools for liver fibrosis in non-Alcoholic Fatty Liver Disease. Methods: This prospective, cross-sectional study included 120 MAFLD patients confirmed via imaging. FibroScan was used to assess liver stiffness, with cutoffs of >8.0 kPa and >12.0 kPa for significant (F2) and advanced (F3) fibrosis, respectively. APRI and FIB-4 scores were calculated using routine clinical parameters. Diagnostic accuracy was assessed using AUROCs, sensitivity, specificity, and correlation with histological fibrosis scores. Results: FibroScan showed the highest accuracy (AUROC: 0.88 for F2, 0.91 for F3), followed by FIB-4 (0.79 for F2, 0.80 for F3) and APRI (0.75 for F2, 0.78 for F3). FibroScan demonstrated the strongest correlation with histological fibrosis (ρ = 0.72), while FIB-4 (ρ = 0.68) outperformed APRI (ρ = 0.64). Obesity and advanced age reduced sensitivity, particularly for FIB-4 and APRI. Conclusion: FibroScan is the most accurate tool for non-invasive fibrosis assessment in MAFLD. FIB-4 provides a reliable, cost-effective alternative, while APRI serves as a simpler screening option, especially in resource-limited settings. These findings support integrating these tools into clinical practice to reduce reliance on liver biopsy